WELDING SOFTSKILL DEVELOPMENT AT THE KARANG TARUNA HARAPAN BARU IN LANGSA CITY - Yani Rizal; Safrizal; Miswar (Global Science Society, 2022)
One of the youth organizations in Gampong Pb. Blang Pase is an organization called Karang Taruna Harapan Baru, which was established in 2018. One of the goals of establishing Karang Taruna in the Minister of Social Affairs Decree no. 25 of 2019 is to develop the spirit and spirit of social entrepreneurship of the younger generation towards independence in an effort to improve Social Welfare.Efforts to improve the quality of human resources, the role of education has a large enough contribution to a nation. Community welfare will increase when human resources are able to manage existing natural resources effectively and efficiently. Langsa City is one area that is trying hard to improve the quality of formal and non-formal education. The activity aims to provide knowledge to youth who take part in this program about the importance of improving soft skills in order to develop an entrepreneurial spirit and reduce unemployment in Pb Village. Langsa City Blang Pase. Provide training to improve basic metal welding soft skills, which will be guided by experienced instructors in the metal welding field. Provide opportunities for training participants to make welding products that have a selling value, so that later they can be sustainable. Provide knowledge on how to start an independent business, good and correct business management so that it can be a provision in the future.